2018
DOI: 10.1159/000486969
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Proteomic Profile of Acquired Enamel Pellicles as a Function of Their Time of Formation and Hydrochloric Acid Exposure

Abstract: Objective: Changes in the protein profile of acquired enamel pellicles (AEP) formed in vivo over different time periods were evaluated after the application of hydrochloric acid (HCl). Methods: Nine subjects were submitted to dental prophylaxis with pumice. After 3 or 120 min, the teeth were isolated with cotton rolls and 50 μL of 0.1 M HCl (pH 1.0), 0.01 M HCl (pH 2.0), or deionized water were applied on the buccal surface of the teeth for 10 s. The AEP was then collected using an electrode filter paper preso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Most published methods for in vivo‐biofilm analyses include mechanical elution by rubbing the dental surface with filter papers. [ 14,19,20,22,25–28,52 ] These protocols imply weak points like relatively poor elution yields and the need to recover the rubbed proteins from the used filter papers. Consequently the eluted protein amounts are comparatively low and necessitate the use of pooled samples from several subjects, preventing insights in individual proteomic profiles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most published methods for in vivo‐biofilm analyses include mechanical elution by rubbing the dental surface with filter papers. [ 14,19,20,22,25–28,52 ] These protocols imply weak points like relatively poor elution yields and the need to recover the rubbed proteins from the used filter papers. Consequently the eluted protein amounts are comparatively low and necessitate the use of pooled samples from several subjects, preventing insights in individual proteomic profiles.…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] In some studies, the identified proteins were classified according to their biological function, origin, and molecular interaction. [ 14,25,28,29 ] However, due to the deficiency of individual proteomic profiles and the analysis of the corresponding saliva, no trends of favored protein adsorptions based on these classifications were revealed. Two recent in situ‐studies focused on the characterization of the individual 3‐min pellicle proteome formed on ceramics specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, statherin is reduced in the AEP in eroded teeth compared to healthy teeth in the same individual . Interestingly, statherin is resistant to removal from the AEP by HCl although only to short, 10 s exposures [Taira et al, 2018]. However, the reduced protein in the AEP measured in this study has not been attributed to reduction in specific protein/s.…”
Section: Discussionmentioning
confidence: 49%
“…Laboratory studies have shown that saliva can play a greater protective role against citric acid than HCl [Wiegand et al, 2008]. TPCs have been observed to remain high after acid exposure suggesting that the HCl penetrates through the pellicle [Taira et al, 2018]. Interestingly, statherin has been observed to remain stable after HCl exposure which is different to the in vivo studies testing dietary acids [Taira et al, 2018].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation